2022
DOI: 10.3389/fnins.2022.904309
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in White Matter Fiber Tracts Characterized by Automated Fiber-Tract Quantification and Their Correlations With Cognitive Impairment in Neuromyelitis Optica Spectrum Disorder Patients

Abstract: ObjectivesTo investigate whether patients with neuromyelitis optica spectrum disorder (NMOSD) have tract-specific alterations in the white matter (WM) and the correlations between the alterations and cognitive impairment.Materials and MethodsIn total, 40 patients with NMOSD and 20 healthy controls (HCs) who underwent diffusion tensor imaging (DTI) scan and neuropsychological scale assessments were enrolled. Automated fiber-tract quantification (AFQ) was applied to identify and quantify 100 equally spaced nodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…First, nodal property decreases are straightforward, as they are related to inflammatory white matter lesions ( 5 , 29 ) and network disconnection ( 28 , 30 ), resulting in corresponding clinical functional impairments ( 31 ). The NMOSD patients in our study experienced fatigue, mild disability, and mild cognitive impairment, which are common clinical symptoms of NMOSD ( 1 , 27 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, nodal property decreases are straightforward, as they are related to inflammatory white matter lesions ( 5 , 29 ) and network disconnection ( 28 , 30 ), resulting in corresponding clinical functional impairments ( 31 ). The NMOSD patients in our study experienced fatigue, mild disability, and mild cognitive impairment, which are common clinical symptoms of NMOSD ( 1 , 27 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also a powerful tool for studying the underlying pathological mechanisms of NMOSD when combined with others novel neuroimaging approaches. For instance, some studies have found that NMOSD patients exhibit increased morphological connectivity in the primary motor modules and motor-sensory related areas of the cerebellum ( 4 ), while white matter fiber bundles such as the thalamic radiation, corticospinal tracts, and dorsal and ventral longitudinal fasciculi are damaged ( 5 ), leading to decreased local connectivity efficiency ( 6 ). However, the alterations in brain structure and function, as well as the mechanisms of plasticity in NMOSD patients, are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…AFQ has been applied to show the changes in diffusion tensor-based measures along white matter fiber tract in cerebral small vessel disease (Huang et al 2020 ), epilepsy (Kreilkamp et al 2019 ), Alzheimer’s disease (Zhang et al 2019 ; Xue et al 2019 ; Dou et al 2020 ; Chen et al 2020 ), neuropsychiatric disorders (Sacchet et al 2014a , b ; Zhang et al 2022a ), neuromyelitis optica spectrum disorder (Yan et al 2022 ), fragile X syndrome (Hall et al 2016 ), and amyotrophic lateral sclerosis (Sarica et al 2017 ) (Fig. 8 ), as well as in obese adolescents (Carbine et al 2020 ), children with attention-deficit/hyperactivity disorder (Lin et al 2020 ) and dyslexia (Banfi et al 2019 ), and neonates at risk of stuttering (Packman et al 2022 ).…”
Section: Traculamentioning
confidence: 99%
“…Therefore, WM degeneration is an effective biomarker for MCI. Diffusion tensor imaging (DTI) is an important tool for studying the microstructure of the brain, which can examine the fine structural changes in WM fibers and provide highly specific anatomical information [5][6][7]. DTI diffusion tensor parameters include fractional anisotropy (FA), mean diffusivity (MD), radial diffusivity (RD), and so on.…”
Section: Introductionmentioning
confidence: 99%